Pertimbangan Hakim dalam Penetapan Dispensasi Perkawinan Dini Akibat Hamil di Luar Nikah pada Pengadilan Agama Bantul - Bagya Agung Prabowo (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research aims to analyze the following issues: first, KHI or Compilation of Islamic Laws as a base of consideration for the judge to determine the dispensation towards early marriage – particularly the one due to the illegal pregnancy and second, the law implication towards the establishment of dispensation for the early marriage due to the illegal pregnancy at Religious Court in Bantul. This research is conducted using a field survey method along with the techniques of interview, observation and library research. The method of the research is a judicial-normative one. The result of the research shows that: first, the consideration of a judge in determining the dispensation of an early marriage is classified into two: legal consideration and public equity consideration. The legal consideration here means that when a judge issues his or her legal determination, it must be in accordance with the proposed legal arguments and evidences. Meanwhile, public equity consideration deals with fact that a marriage frequently is considered as an alternative solution for the coming social issues. Another consideration of a judge is that the one who will get married is the biological father of the infant conceived. Second, the dispensation of the early marriage needs to be more tightened in consideration to the increasing underage marriage.